Public administration as a design science - Shangraw, Ralph F., Jr.; Crow, Michael M. (1998)
This article examines Herbert Simon's notion of a "design" science and discusses its applicability to the field of public administration. Public administration, as a design science, exists at the nexus between the inner and outer environments of public organizations. As such, it integrates and synthesizes theories and propositions from other disciplines including the behavioral sciences, the system sciences, and the natural sciences. In addition to being concerned with descriptive aspects of the field, public administration scholars must be willing to prescribe, to design, and to redesign public sector systems. A framework for assessing design opportunities is developed, and the questions raised by this approach are addressed. - Reproduced
Keywords: Public administration